The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/13621718.2017.1376792
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two types of low-transformation-temperature weld metals based on solidification mode

Abstract: Two types of low-transformation-temperature weld metals were devised, one associated with primary austenite solidification, the other primary ferrite solidification. The martensite start temperature of both low-transformation-temperature weld metals was about 125°C. Experimental results showed that low-transformation-temperature weld microstructure associated with primary austenite solidification was martensite with 8.0% retained austenite, whereas that one related to primary ferrite solidification primarily c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…In particular, the proof that compressive residual stresses are formed [3,4], the investigation of the mechanisms of stress formation [5,6], and the effect on the fatigue strength [7,8] have been the subject of many research projects. Recent publications also deal with extended topics such as microstructure and the associated mechanical properties [9][10][11][12][13], the behaviour during multilayer welding [14][15][16][17][18], and the application of LTT in beam welding [19].…”
Section: Ltt Filler Metalsmentioning
confidence: 99%
“…In particular, the proof that compressive residual stresses are formed [3,4], the investigation of the mechanisms of stress formation [5,6], and the effect on the fatigue strength [7,8] have been the subject of many research projects. Recent publications also deal with extended topics such as microstructure and the associated mechanical properties [9][10][11][12][13], the behaviour during multilayer welding [14][15][16][17][18], and the application of LTT in beam welding [19].…”
Section: Ltt Filler Metalsmentioning
confidence: 99%
“…It is well-known that tensile welding residual stress is detrimental to the fatigue strength of welded joint [28,29]. To minimize the unfavorable tensile stress, the low transformation temperature (LTT) alloys, which take advantage of martensitic transformation, have been developed during the past two decades [30][31][32]. Furthermore, it has been investigated that an elongated weld method overlaying LTT weld metal on the corner boxing fillet-welded joints can greatly enhance fatigue lives to at least 4 times [33].…”
Section: Thermal Cycles In Elongated Weld With Low Transformation Temmentioning
confidence: 99%
“…Secondly, the volume fraction of RA is 7.80% of the LN, while it is 3.26% of the HN. Many researchers [47,48] have reported that the presence of RA is a significant role in improving toughness. During deformation, soft austenite can release internal stress and inhibit crack initiation.…”
Section: Toughness Of Deposited Metalsmentioning
confidence: 99%